Prevalence of acute coronary syndrome among patients presenting - Mobarok Hossen; Shamsul Islam; Kawser Hamid; Enamul Kabir Khan; Mohammad Nazmul Haq; Shanaz Pervin (Central Medical College Journal, 2025)
Background: Acute coronary syndrome (ACS) remains a major cause of morbidity and mortality worldwide, with various risk factors contributing to its prevalence. This study aimed to assess the prevalence of ACS among patients presenting with chest pain at a tertiary care cardiac center in Cumilla, Bangladesh. Methods: A cross-sectional observational study was conducted at Eastern Medical College and Hospital, Cumilla, from July 2023 to June 2024. A total of 300 patients, diagnosed with ACS based on clinical, electrocardiographic, and biochemical criteria, were included. Demographic characteristics, risk factors, clinical presentations, ACS subtypes, and management strategies were analyzed. Data were analyzed using descriptive and inferential statistical methods. Results: The study population predominantly consisted of male patients (70%) with a mean age of 52.8 years. The highest prevalence of ACS was observed in patients aged 40–59 years (50%), followed by those ≥60 years (30%). The most common risk factors for ACS included hypertension (60%), smoking (50%), and diabetes mellitus (40%). The most prevalent ACS subtype was ST-segment elevation myocardial infarction (STEMI) (45%), followed by non-ST-segment elevation myocardial infarction (NSTEMI) (35%) and unstable angina (20%). Chest pain was the predominant symptom in all patients (100%), while other common symptoms included dyspnea (30%) and nausea/vomiting (20%). In terms of management, 50% of patients received thrombolysis, 25% underwent percutaneous coronary intervention (PCI), and 10% required coronary artery bypass grafting (CABG). Short-term outcomes revealed a high discharge rate (90%) and an in-hospital mortality rate of 10%. Conclusion: This study's findings show a considerable prevalence of ACS, a greater incidence of STEMI, and a clear connection with modifiable risk factors such as hypertension, diabetes, and smoking. Early intervention, such as thrombolysis and PCI, resulted in much better short-term outcomes. Bangladesh urgently requires public health efforts to prevent and manage ACS risk factors. Central Medical College Journal Vol 8 No 2 July 2024 Page: 75-81